Speculative asset price dynamics and wealth taxes - Sarah Mignot; Fabio Tramontana; Frank Westerhoff (Decisions in Economics and Finance, 2021)
Based on the seminal asset-pricing model by Brock and Hommes (J Econ Dyn Control 22:1235–1274, 1998), we analytically show that higher wealth taxes increase the risky asset's fundamental value, enlarge its local stability domain, may prevent the birth of nonfundamental steady states and, if they exist, reduce the risky asset's mispricing. We furthermore find that higher wealth taxes may hinder the emergence of endogenous asset price oscillations and, if they exist, dampen their amplitudes. Since oscillatory price dynamics may be associated with lower mispricing than locally stable nonfundamental steady states, policymakers may not always want to suppress them by imposing (too low) wealth taxes. Overall, however, our study suggests that wealth taxes tend to stabilize the dynamics of financial markets.
Keywords: D84; G12; G18; G41; 330; Asset price dynamics; Wealth taxes; Heterogeneous expectations; Nonlinear dynamics; Stability and bifurcation analysis